HYDROALCOHOLIC EXTRACT OF SWERTIA CHIRATA AND SWERTIA CORDATA ATTENUATES HYPOXIA-MEDIATED MEMORY DYSFUNCTION BY IMPROVING NEURONAL SURVIVAL IN WISTAR RATS - KAUSHAL, KRITIKA; SINGH, HARVINDER; KANT, ANIL (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Swertia chirata and Swertia cordata have been used in traditional and folk medicines to treat several mental disorders. However, the mechanistic and experimental justification to its traditional use is lacking. The present study was aimed to investigate the neuromodulatory potential of S. chirata and S. cordata during hypoxia-induced neuronal damage in Wistar rats and to determine the underlying mechanism. Methods: Animals were divided into six groups (n=5). Hypoxia was inflicted by subjecting animals to the atmosphere having 10% O2 for 3 days. Animals were administered 100 mg/kg hydroalcoholic extract of S. chirata and S. cordata orally once daily for 7 days, after which motor coordination (Rotarod test) and memory functions (active avoidance test and passive avoidance test) were evaluated. Animals were sacrificed and biochemical investigations for oxidative stress and histopathology were performed. Results: Subjecting animals to hypoxia resulted in marked memory dysfunction, and extract treatments improved memory functions in active avoidance and passive avoidance task. Hypoxiainduced the marked oxidative stress as indicated by the significantly elevated reactive oxygen species and lipid peroxidation and depleted catalase and glutathione levels in the hippocampus. S. chirata and S. cordata treatment alleviated oxidative stress in the hippocampus region of the brain. Brain histopathology confirmed that hypoxia resulted in significant neuronal damage and extract treatment efficiently rescued neurons from hypoxic damage. Overall, S. chirata extract treatment was observed to have better neuromodulatory effect than S. cordata during hypoxia. Conclusion: Hypoxia induced memory dysfunction by inflicting neuronal damage and oxidative stress in the hippocampus region of the brain. The hydroalcoholic extract of S. chirata and S. cordata improved memory functions in hypoxic animals by alleviating hippocampal oxidative stress and by improving neuronal morphology and survival.